2013
DOI: 10.3892/ijo.2013.1978
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor activity of cerulenin combined with oxaliplatin in human colon cancer cells

Abstract: Fatty acid synthase is highly expressed in many types of human cancers. Cerulenin, a natural inhibitor of fatty acid synthase, induced apoptosis in the human colon cancer cell lines HCT116 and RKO. Oxaliplatin also induced cell death in these cell lines. Cerulenin treatment was associated with reduced levels of phosphorylated Akt, activation of p38 and induced caspase-3 cleavage and finally caused apoptosis. Oxaliplatin induced activation of the p53-p21 pathway and p38. In combination with cerulenin and oxalip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…It has been suggested that inhibiting FASN pharmacologically reduces cell growth and survival, and induces the apoptosis of colon cancer cells (34). For example, cerulenin, a natural FASN inhibitor, enhances antitumor activity when combined with oxaliplatin in human colon cancer cells (35) and suppresses liver metastasis of colon cancer (36). C75, a stable synthetic small molecule developed specifically for inhibiting FASN, produces a cytotoxic effect modulated by p53 in colon carcinoma cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that inhibiting FASN pharmacologically reduces cell growth and survival, and induces the apoptosis of colon cancer cells (34). For example, cerulenin, a natural FASN inhibitor, enhances antitumor activity when combined with oxaliplatin in human colon cancer cells (35) and suppresses liver metastasis of colon cancer (36). C75, a stable synthetic small molecule developed specifically for inhibiting FASN, produces a cytotoxic effect modulated by p53 in colon carcinoma cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…12 Inversely, downregulation of AKT signaling reduces the dose of L-OHP and is considered to endure the chemotherapy. 13 Some genes are known to regulate AKT pathway nowadays. For instance, erb-b2 receptor tyrosine kinase 4 (ERBB4) is acknowledged to upregulate the activation of AKT signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Together with our recent reports on regulation of AKT by cPLA 2 α and its enzymatic products [20], these findings suggest the presence of feed-forward loop between AKT and lipid modifying enzymes that favours cancer cell proliferation. Not surprisingly, it has been suggested that chemotherapy targeting both AKT signaling and lipid metabolism might be of benefit [39, 40]. …”
Section: Discussionmentioning
confidence: 99%